2020
DOI: 10.1091/mbc.e20-01-0058
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic streaming drifts the polarity cue and enables posteriorization of theCaenorhabditis eleganszygote at the side opposite of sperm entry

Abstract: Cell polarization is required to define body axes during development. The position of spatial cues for polarization is critical to direct the body axes. In Caenorhabditis elegans zygotes, the sperm-derived pronucleus/centrosome complex (SPCC) serves as the spatial cue to specify the anterior-posterior axis. Approximately 30 minutes after fertilization, the contractility of the cell cortex is relaxed near the SPCC, which is the earliest sign of polarization and called symmetry breaking (SB). It is unclear how t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
(63 reference statements)
2
16
0
Order By: Relevance
“…A similar mechanism of MT-dependent cytoplasmic streaming exists in the C. elegans zygote, but here the alignment of MTs relies on the endoplasmic reticulum [32][33][34]. This meiotic cytoplasmic streaming (MeiCS) influences the position of the sperm-derived pronucleus (PN) and associated centrosomes (PN/centrosome complex), which will determine the antero-posterior axis (AP axis) of the C. elegans embryo [35][36][37][38].…”
Section: Introductionmentioning
confidence: 94%
“…A similar mechanism of MT-dependent cytoplasmic streaming exists in the C. elegans zygote, but here the alignment of MTs relies on the endoplasmic reticulum [32][33][34]. This meiotic cytoplasmic streaming (MeiCS) influences the position of the sperm-derived pronucleus (PN) and associated centrosomes (PN/centrosome complex), which will determine the antero-posterior axis (AP axis) of the C. elegans embryo [35][36][37][38].…”
Section: Introductionmentioning
confidence: 94%
“…adjacent to the male pronucleus, towards the cell cortex (Wallenfang and Seydoux, 2000;Kimura and Kimura, 2020;Bienkowska and Cowan, 2012). We capture the impact of these interactions by a drag coefficient between the male pronucleus and the cortical layer (d, see SI: Equation 18 and SI: subsubsection 2.1.2).…”
Section: A Mathematical Model Accounts For Ap Axis Convergencementioning
confidence: 99%
“…Cytoplasmic flows, in turn, could transport the male pronucleus (Kimura and Kimura, 2020;Mittasch et al, 2018) towards the closest tip. We refer to this scenario as the cytoplasmic flow-dependent mechanism.…”
mentioning
confidence: 99%
“…Consistent with the role of centrosomes in polarity induction, SB in cortical contractility will occur from the cortex closest to the position of the centrosomes in the zygote (Bienkowska and Cowan, 2012 ). Even in mutant zygotes with the centrosomes located near the maternal pronucleus during meiosis, SB is always triggered from the cortex proximally to the centrosomes, which results in the establishment of a reversed pattern of cortical flow and PAR distribution (Goldstein and Hird, 1996 ; Kimura and Kimura, 2020 ). These findings indicate that zygote polarization is induced by centrosomes.…”
Section: Induction Of Sb By the Centrosomementioning
confidence: 99%
“…During cytoplasmic streaming, kinesin-1 transports a network of endoplasmic reticula toward the plus end of the microtubule (Kimura et al, 2017 ). If by chance cytoplasmic streaming moves the centrosome–pronucleus complex away from the sperm-entry site toward the opposite pole, where the maternal pronucleus is generally located, the centrosome can induce SB at the cortex opposite to the sperm-entry site (Kimura and Kimura, 2020 ). These observations confirmed that the position of the centrosome at the time of SB, but not the sperm-entry site, specifies the anteroposterior axis.…”
Section: Ensuring the Position Of The Centrosome For Efficient Sbmentioning
confidence: 99%